Dialogic action in climate change discussions: An international study of high school students in China, New Zealand, Norway and the United States - Arya, Diana J.; Parker, Jessica K. (Dialogic Pedagogy, 2015)
Global efforts to prepare young developing minds for solving current and future challenges of climate change have advocated interdisciplinary, issues-based instructional approaches in order to transform traditional models of science education as delivering conceptual facts (UNESCO, 2014). This study is an exploration of the online interactions in an international social network of high school students residing in Norway, China, New Zealand and the United States (N=141). Students participated in classroom-based and asynchronous online discussions about adapted versions of seminal scientific studies with facilitative support from seven scientists across various fields. Grounded in a language-in-use frame for investigating facilitation and demonstrations of problem-based and evidence-based reasoning (Kelly & Chen, 1999), we traced the varied questions, assertions, and evidentiary sources within student-led online discussions. We found that questions from scientific experts in the form of unconstrained, open-ended invitations for exploration were followed by students’ acknowledgement and consideration of complex and, at times, conflicting sociopolitical and economic positions about climate change issues. These findings suggest that broadening science classroom discussions to include socially relevant, unsolved issues like climate change could open potential entry points for a dialogic approach that fosters a scientific community in the classroom.
Keywords: C:China; C:New Zealand; C:Norway; C:United States; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change discussions; oa:sdg:13 Climate action; oa:topic:T10636 Self-Regulated Learning in Educational Research; oa:topic:T11715 Impact of Instructional Interventions on Critical Thinking Skills; oa:topic:T12887 Development of Personal Epistemological Beliefs; openalex:import; openalex:yes